Micro-macro linkages between gender, development, and growth : implications for the Caribbean region - Seguino, Stephanie (2008)
Explores the channels by which gender inequality affects, and in important ways, constrains economic development and growth in the Caribbean region. Explores further, the endogeneity of gender inequality to the macroeconomic policy environment. Discusses economic policies that can promote greater gender equality and economic development and growth.